Flying solo : a novel - Holmes, Linda (Radio talk show host) (Ballantine Books, 2022)
"A woman returns to her small Maine hometown, uncovering family secrets that take her on a journey of self-discovery and new love, in this warm and charming novel from the New York Times bestselling author of Evvie Drake Starts Over. Smarting from her recently cancelled wedding and about to turn forty, Laurie Sassalyn returns to her Maine hometown of Calcasset to handle the estate of her great-aunt Dot, a spirited adventurer who lived to be ninety. Along with boxes of Polaroids and pottery, a mysterious wooden duck shows up at the bottom of a cedar chest. Laurie's curiosity is piqued, especially after she finds a love letter to the never-married Dot that ends with the line, "And anyway, if you're ever desperate, there are always ducks, darling." Laurie is told that the duck has no financial value. But after it disappears under suspicious circumstances, she feels compelled to figure out why anyone would steal a wooden duck-and why Dot kept it hidden away in the first place. Suddenly Laurie finds herself swept up in a righteous caper that has her negotiating with antiques dealers and con artists, going on after-hours dates at the local library, and reconnecting with her oldest friend and first love. Desperate to uncover her great-aunt's secrets, Laurie must reckon with her past, her future, and ultimately embrace her own vision of flying solo"--